Ischemic priapism induced by a fixed drug combination of tamsulosin and tadalafil - Leonson, Libin Sanjeev; Dixit, Vimal; Chaudhury, Annwesha; Jain, Ayush; Dwivedi, Shikha (International Journal of Basic & Clinical Pharmacology, 2025)
Priapism, a persistent erection lasting more than 4 hours, can be caused by various factors, including medications. This case report presents a 23-year-old male who developed ischemic priapism after taking tablet Contiflo-T, a combination of tamsulosin and tadalafil. The patient required multiple interventions, including aspiration and intracavernosal phenylephrine injections, to resolve the condition. The combination of these drugs, which are commonly used for urinary tract symptoms and erectile dysfunction, likely contributed to the priapism by increasing blood flow to the penis and preventing its return to a flaccid state. This case highlights the potential for adverse drug interactions and the importance of careful monitoring when prescribing medications for these conditions.